In the wake of the supermarket 'milk wars': Media, farmers and the power of pastoral sentimentality. (December 2019) - Phillipov, Michelle; Loyer, Jessica
Abstract: On Australia Day in 2011, Australian supermarket giant, Coles, announced that it was slashing the price of its own-brand milk to a considerably discounted 1/litre, a move immediately matched by rival Woolworths. The retailers, who had anticipated that low prices would be viewed as unequivocally good for consumers, found themselves at the centre of an unexpected media backlash and the subjects of a sustained campaign by the dairy industry to expose the threat of major supermarkets to Australian dairy livelihoods. This paper analyses the news coverage that emerged as a result of the events now dubbed the 'milk wars'. Through discourse analysis of Australian news stories, we show how the media coverage of milk pricing—and the dairy industry campaigns that underpinned it—sought to galvanise media and public support through specific images and discourses associated with the 'Australian farmer'. We argue that the discourses and images used most frequently by the dairy industry and which had most cut-through with media were those most strongly invested in Australian pastoral sentimentality: images of traditional, 'small-scale', multi-generational family farmers being tragically forced off their land by the supermarket duopoly. We show how this coverage reveals the power of romanticised depictions of farming as a media strategy for galvanising public support for farmers' livelihoods, but in their focus on (certain types of) farmers and farming practices as 'worthy' of public and media concern, these depictions were ultimately co-opted by supermarket marketing campaigns designed to silence critique. That proponents of alternative food politics continue to mobilise discourses of pastoral sentimentality as a means to encourage (urban) consumer support raises questions about the effectiveness of such discourses to meaningfully oppose corporate power in the food system.